Particle-like representation for the field of a moving point charge in nonlinear electrodynamics. (25th April 2017) - Gitman, D M; Shabad, A E; Shishmarev, A A
Abstract: In a simple nonlinear model stemming from quantum electrodynamics wherein the pointlike charge has finite field-self-energy, we demonstrate that the latter can be presented as a soliton with its energy–momentum vector satisfying the standard mechanical relation characteristic of a free moving massive relativistic particle.